Novel Boronate Probe Based on 3-Benzothiazol-2-yl-7-hydroxy-chromen-2-one for the Detection of Peroxynitrite and Hypochlorite - Julia Modrzejewska; Marcin Szala; Aleksandra Grzelakowska; Małgorzata Zakłos-Szyda; Jacek Zielonka; Radosław Podsiadły (Molecules, 2021)
Derivatives of coumarin, containing oxidant-sensitive boronate group, were recently developed for fluorescent detection of inflammatory oxidants. Here, we report the synthesis and the characterization of 3-(2-benzothiazolyl)-7-coumarin boronic acid pinacol ester (BC-BE) as a fluorescent probe for the detection of peroxynitrite (ONOO–), with high stability and a fast response time. The BC-BE probe hydrolyzes in phosphate buffer to 3-(2-benzothiazolyl)-7-coumarin boronic acid (BC-BA) which is stable in the solution even after a prolonged incubation time (24 h). BC-BA is slowly oxidized by H2O2 to form the phenolic product, 3-benzothiazol-2-yl-7-hydroxy-chromen-2-one (BC-OH). On the other hand, the BC-BA probe reacts rapidly with ONOO−. The ability of the BC-BA probe to detect ONOO– was measured using both authentic ONOO– and the system co-generating steady-state fluxes of O2•– and •NO. BC-BA is oxidized by ONOO– to BC-OH. However, in this reaction 3-benzothiazol-2-yl-chromen-2-one (BC-H) is formed in the minor pathway, as a peroxynitrite-specific product. BC-OH is also formed in the reaction of BC-BA with HOCl, and subsequent reaction of BC-OH with HOCl leads to the formation of a chlorinated phenolic product, which could be used as a specific product for HOCl. We conclude that BC-BA shows potential as an improved fluorescent probe for the detection of peroxynitrite and hypochlorite in biological settings. Complementation of the fluorescence measurements by HPLC-based identification of oxidant-specific products will help to identify the oxidants detected.